Mathematical and computational modeling of tomato growth for 3D printing - Streda, Maiara Andressa (2024)
The physical appearance of food has a significant impact on its consumption and economic value. Research indicates consumer dissatisfaction with the quality of the tomatoes found in commerce. Physical appearance is the main characteristic that causes dissatisfaction among consumers looking for unblemished fruits. In view of this, this work aims to create a parametric model for the 3D printing of tomato fruit development that helps the producer identify the development phases of their production and compare the morphological characteristics of the fruits. For this purpose, daily experimental data on fruit growth were extracted, in addition to photographic records. In this study, a model was developed that describes the growth of fruits of the hybrid saladette tomato SM-16. This model simulates the daily growth behavior of these fruits. The mathematical and computational modeling was developed using the Python programming language and two other free software, Octave and Inkscape. The growth of the tomato is represented by a logistic model, while the shape of the fruits during growth is a model developed in Artificial Neural Network. The models used, adjusted to the parameters found, proved to be adequate to describe the growth behavior of the tomato fruits of the variety studied over time.